Intergenerational Transmission of Parent Encouragement to Diet From Adolescence Into Adulthood - Berge, Jerica M. (Pediatrics, 2018)
BACKGROUND: Although previous cross-sectional research has revealed potential harmful outcomes associated with parent encouragement to diet, it is unclear whether these effects are long lasting and whether they are transmitted to the next generation. The main aim of the current study was to examine longitudinal associations between exposure to parent encouragement to diet in adolescence and weight-related and emotional health outcomes in adulthood and to examine whether intergenerational transmission of encouragement to diet occurs. METHODS: This is a longitudinal, population-based study (ie, Project Eating and Activity in Teens and Young Adults) of socioeconomically and racially and/or ethnically diverse adolescents managed into adulthood and/or parenthood (n = 556; mean age = 31.4; 64.6% female). Surveys and anthropometrics were completed at school by adolescents in 1998–1999 and surveys were completed online in 2015–2016 by young adults. RESULTS: Experiencing parent encouragement to diet as an adolescent was significantly associated with a higher risk of overweight or obesity, dieting, binge eating, engaging in unhealthy weight control behaviors, and lower body satisfaction 15 years later as a parent, after adjusting for sociodemographics and baseline measures of the outcomes (P < .05). Additionally, intergenerational transmission of encouragement to diet occurred and resulted in parents being more likely to report other weight-focused communication in the home environment. CONCLUSIONS: Exposure to parent encouragement to diet as an adolescent had long-term harmful associations with weight-related and emotional health outcomes in parenthood and was transmitted to the next generation. It may be important for health care providers to educate parents about the potential harmful and long-lasting consequences of engaging in encouragement to diet with their children.